Electrolyte, preparation method thereof and aluminum electrolytic capacitor
By adding super-hydrophilic nanomodified silica sol to the electrolyte, the problem of the electrolyte's conductivity and flash fire voltage drop after high-temperature storage is solved, and the high-temperature storage performance of the electrolyte is improved.
Patent Information
- Application Number
- CN202411602861.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-18
AI Technical Summary
After the existing electrolyte is stored at high temperature, its conductivity decreases and the flash fire voltage also decreases, resulting in deterioration of capacitor performance.
The superhydrophilic nanomodified silica sol is added to the electrolyte. Through compatibility and bonding with the macromolecular carboxylic acid, the solubility and high-temperature stability of the macromolecular carboxylic acid are improved, thereby improving the high-temperature storage performance of the electrolyte.
It effectively reduces the conductivity reduction rate of the electrolyte after high temperature storage, maintains or increases the flash fire voltage, and significantly improves the high-temperature storage performance of the electrolyte.
Smart Images

Figure BDA0005128754580000141
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of capacitor electrolytes, and in particular relates to an electrolyte and a preparation method thereof, and an aluminum electrolytic capacitor. Background Art
[0002] The macromolecular carboxylic acid in the electrolyte is easily adsorbed by the alumina film. The macromolecular carboxylic acid ionizes into anions in the solvent, and under the action of the electric field, it is directionally adsorbed to the anode surface to form an adsorption layer. This adsorption layer has the function of shielding the electric field and makes the electric field acting on the electrode uniform, eliminating the edge effect and increasing the flash voltage of the electrolyte.
[0003] In traditional electrolyte preparation materials, the most effective way to increase the flash voltage of the electrolyte is to add macromolecular carboxylic acid to form an adsorption layer on the anode surface. However, macromolecular carboxylic acid will inevitably increase the viscosity and resistivity of the electrolyte due to its poor solubility. In addition, macromolecular carboxylic acid has poor stability at high temperatures and is easily decomposed and oxidized, resulting in a decrease in flash voltage and conductivity after high-temperature storage or use in a high-temperature environment. The macromolecular carboxylic acid cannot play its role, and the performance of the capacitor is seriously degraded, which is not conducive to the performance of the capacitor. Therefore, the existing electrolyte still needs to be improved. Summary of the invention
[0004] The main purpose of the present invention is to provide an electrolyte, a preparation method thereof and an aluminum electrolytic capacitor. The addition of super-hydrophilic nano-modified silica sol in the electrolyte of the present invention reduces the rate of decrease of the conductivity of the electrolyte after high-temperature storage, and the flash voltage after high-temperature storage is basically maintained at the same level as before storage or even higher than before storage, which significantly improves the high-temperature storage performance of the electrolyte.
[0005] In order to achieve the above objectives, the present invention provides the following technical solutions.
[0006] In a first aspect, the present invention provides an electrolyte comprising a main solvent, an auxiliary solvent, a solute, an auxiliary solute and a flash voltage enhancer, wherein the flash voltage enhancer comprises a super-hydrophilic nano-modified silica sol, and based on the total mass of the raw materials forming the electrolyte, the mass percentage of the flash voltage enhancer is 10% to 18%.
[0007] In some embodiments of the present invention, based on the total mass of the raw materials forming the electrolyte, the mass percentage of the main solvent is 30% to 50%, the mass percentage of the auxiliary solvent is 1% to 5%, the mass percentage of the solute is 25% to 38%, and the mass percentage of the auxiliary solute is 2.6% to 4.2%.
[0008] In some embodiments of the present invention, the super-hydrophilic nano-modified silica sol is obtained by reacting acidic cross-linked super-hydrophilic nano-modified silica with an aqueous transparent resin.
[0009] In some embodiments of the present invention, the water-based transparent resin includes at least one of a water-based polyacrylic resin, a water-based fluorocarbon resin, a water-based amino resin, a water-based epoxy resin, and a water-based polyurethane resin.
[0010] In some embodiments of the present invention, the main solvent includes at least one of ethylene glycol, tripropylene glycol, diethylene glycol, propylene glycol, and glycerol.
[0011] In some embodiments of the present invention, the auxiliary solvent includes at least one of alcohols, alcohol ethers, amides, lactones, sulfolane, N-methylpyrrolidone, and dimethyl sulfoxide.
[0012] In some embodiments of the present invention, the solute includes at least one of a straight-chain or branched dicarboxylic acid containing 8 to 30 carbon atoms and its ammonium salt, a monocarboxylic or polycarboxylic acid containing a benzene ring and its ammonium salt, dimethylamine, diethylamine, and triethylamine.
[0013] In some embodiments of the present invention, the solute includes one or more of ammonium suberate, ammonium azelaic acid, ammonium sebacate, ammonium dodecanedioate, C14, C16, C24, C30 fatty acids with single-end side branches or double-end side branches and their ammonium salts, dimethylamine, diethylamine, and triethylamine.
[0014] In some embodiments of the present invention, the auxiliary solute includes at least one of a linear polycarboxylic acid containing 5 to 35 carbon atoms and its ammonium salt, boric acid, ammonium borate, and ammonium pentaborate.
[0015] In some embodiments of the present invention, the electrolyte further comprises at least one of a pH regulator, a waterproofing agent, a hydrogen scavenger and a sustained-release agent.
[0016] In some embodiments of the present invention, the pH adjuster is selected from aqueous ammonia.
[0017] In some embodiments of the present invention, the waterproofing mixture includes at least one of borates, phosphates, phosphoric acid, ammonium phosphate, phosphorous acid, ammonium phosphite, hypophosphorous acid, ammonium hypophosphite, ammonium hydrogen phosphate, polyphosphoric acid, ammonium polyphosphate salt, and alkyl phosphate.
[0018] In some embodiments of the present invention, the hydrogen scavenger includes at least one of p-nitrophenol, m-nitrophenol, p-nitrobenzoic acid, o-nitroacetophenone, m-phenol, hydroquinone, o-nitroanisole, and p-nitrobenzyl alcohol.
[0019] In some embodiments of the present invention, the sustained-release agent includes at least one of mannitol, sorbitol, xylitol, and sucrose.
[0020] In some embodiments of the present invention, based on the total mass of the raw materials forming the electrolyte, the mass percentage of the pH regulator is 0.1% to 0.6%, the mass percentage of the waterproof mixture is 0.01% to 0.05%, the mass percentage of the hydrogen scavenger is 0.1% to 0.6%, and the mass percentage of the sustained-release agent is 1% to 4%.
[0021] The second aspect of the present invention provides a method for preparing the electrolyte described in the first aspect, the preparation method comprising: mixing the main solvent and the auxiliary solvent evenly, adding the solute, the auxiliary solute and the flash voltage enhancer at 95°C to 105°C, and stirring until dissolution is complete.
[0022] In some embodiments of the present invention, the preparation method also includes preparing a super-hydrophilic nano-modified silica sol, and the preparation of the super-hydrophilic nano-modified silica sol includes: dissolving the silica sol in an alcohol solvent and adjusting the pH value to 2-3, adding a silicon source precursor, reacting for a period of time under a first heating condition, adding a surfactant, and keeping the reaction warm for a period of time to obtain an acidic cross-linked super-hydrophilic nano-modified silica; reacting the acidic cross-linked super-hydrophilic nano-modified silica with an aqueous transparent resin under a second heating condition to obtain a super-hydrophilic nano-modified silica sol.
[0023] In some embodiments of the present invention, the silicon source precursor includes at least one of tetraethyl orthosilicate and tetramethyl orthosilicate.
[0024] In some embodiments of the present invention, the alcohol solvent is selected from ethylene glycol.
[0025] In some embodiments of the present invention, the surfactant is selected from sodium C14-16 olefin sulfonate.
[0026] In some embodiments of the present invention, the mass ratio of the silicon source precursor to the surfactant is 6.5-8.0:0.5-1.5.
[0027] In some embodiments of the present invention, the first heating temperature is 40°C to 60°C.
[0028] In some embodiments of the present invention, the silicon source precursor is reacted for 1 h to 2 h after being added, and the surfactant is reacted for 24 h to 26 h after being added.
[0029] In some embodiments of the present invention, the mass ratio of the acidic cross-linked super-hydrophilic nano-modified silica to the aqueous transparent resin is 100:1-3.
[0030] In some embodiments of the present invention, the second heating temperature is 30° C. to 50° C., and the second heating time is 2 h to 4 h.
[0031] In some embodiments of the present invention, the preparation method further includes: after the main solvent and the auxiliary solvent are evenly mixed, a solute and a sustained-release agent are added at 95°C to 105°C, and after complete dissolution, a waterproofing agent, a hydrogen scavenger, an auxiliary solute and a flash voltage enhancer are added, the temperature is reduced to 55°C to 65°C, and a pH adjuster is added to obtain the electrolyte.
[0032] In a third aspect, the present invention provides an aluminum electrolytic capacitor, wherein the aluminum electrolytic capacitor uses the electrolyte described in the first aspect or the electrolyte prepared by the preparation method described in the second aspect as a working electrolyte.
[0033] Compared with the prior art, the present invention achieves the following technical effects:
[0034] The addition of super-hydrophilic nano-modified silica sol to the electrolyte of the present invention reduces the rate of decrease in conductivity of the electrolyte after high-temperature storage, and the flash voltage after high-temperature storage is basically maintained at the same level as before storage or even higher than before storage, which significantly improves the high-temperature storage performance of the electrolyte.
[0035] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented according to the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are listed below. DETAILED DESCRIPTION
[0036] The exemplary embodiments of the present invention will be described in more detail below with reference to specific embodiments. It should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.
[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the description and claims of the present invention and any variations thereof are intended to cover non-exclusive inclusions.
[0038] In the description of the embodiments of the present invention, the technical terms "first", "second", etc. are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.
[0039] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0040] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent: A exists, A and B exist at the same time, and B exists. In addition, the character " / " in this document generally indicates that the associated objects before and after are in an "or" relationship.
[0041] In the description of the embodiments of the present invention, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0042] Silica sol is used in the working electrolyte of aluminum capacitors because of its small particle size, charge, uniform dispersion, high purity, excellent high temperature stability and strong adsorption performance. The super-hydrophilic nano-modified silica sol used in the present invention not only has the above advantages of silica sol, but also has a hydrophilic group polarity similar to the carboxylic acid group (-COOH) in the macromolecular carboxylic acid, which is soluble in the surrounding macromolecular carboxylic acid. After bonding, it increases the solubility of the macromolecular carboxylic acid, reduces the viscosity of the electrolyte, and improves the conductivity. And after the two are similarly soluble and combined with each other, the thermal stability of the outermost layer of SiO2 is high, which greatly improves the high temperature stability of the macromolecular carboxylic acid.
[0043] The present invention provides an electrolyte for a high temperature resistant capacitor, the electrolyte comprising a main solvent, an auxiliary solvent, a solute, an auxiliary solute and a flash voltage enhancer, the flash voltage enhancer comprising a super-hydrophilic nano-modified silica sol, and based on the total mass of the raw materials forming the electrolyte, the mass percentage of the flash voltage enhancer is 10% to 18%.
[0044] In the embodiments of the present invention, super-hydrophilic nano-modified silica sol is used as a flash voltage enhancer in the electrolyte. The super-hydrophilic nano-modified silica sol works together with macromolecular carboxylic acid to enhance the solubility of macromolecular carboxylic acid and the conductivity of the electrolyte. The super-hydrophilic nano-modified silica sol enhances the high-temperature stability of macromolecular carboxylic acid and the high-temperature resistance of the capacitor. At the same time, the super-hydrophilic nano-modified silica sol has super strong permeability, which enhances the effect of penetrating into the oxide film of the anode foil, and the oxide film repair reaction is faster. The super-hydrophilic nano-modified silica has excellent stability in the electrolyte system.
[0045] In an embodiment of the present invention, the mass percentage of the flash voltage booster provided by the present invention can be a value in the interval formed by any two values in the above range, for example, it can be 10% to 14%, or 14% to 18%, and so on. The mass percentage of the flash voltage booster provided by the present invention can also be one of 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, or any value that meets the above range.
[0046] In the embodiment of the present invention, the super-hydrophilic nano-modified silica sol is obtained by a synthetic reaction of acidic cross-linked super-hydrophilic nano-modified silica and a water-based transparent resin.
[0047] In some embodiments of the present invention, the water-based transparent resin includes at least one of a water-based polyacrylic resin, a water-based fluorocarbon resin, a water-based amino resin, a water-based epoxy resin, and a water-based polyurethane resin.
[0048] In some embodiments of the present invention, the main solvent may be a polyol, for example, may be at least one selected from ethylene glycol, tripropylene glycol, diethylene glycol, propylene glycol, and glycerol.
[0049] In some embodiments of the present invention, based on the total mass of the raw materials forming the electrolyte, the mass percentage of the main solvent is 30% to 50%. The mass percentage of the main solvent provided by the present invention can be the value of the interval composed of any two values in the above interval, such as 30% to 40%, or 40% to 50%, and so on. The mass percentage of the main solvent provided by the present invention can also be 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50% or any value that meets the above range value.
[0050] In some embodiments of the present invention, the auxiliary solvent includes at least one of alcohols, alcohol ethers, amides, lactones, sulfolane, N-methyl pyrrolidone, and dimethyl sulfoxide. For example, the auxiliary solvent can be selected from one or more of n-butanol, n-octanol, diethylene glycol monobutyl ether, diethylene glycol dimethyl ether, ethylene glycol butyl ether, diethylene glycol diethyl ether, triethylene glycol dimethyl ether, sulfolane, N-methyl pyrrolidone, and dimethyl sulfoxide.
[0051] In some embodiments of the present invention, based on the total mass of the raw materials forming the electrolyte, the mass percentage of the auxiliary solvent is 1% to 5%. The mass percentage of the auxiliary solvent provided by the present invention can be one of 1%, 2%, 3%, 4%, 5% or any value that meets the above range.
[0052] In some embodiments of the present invention, the solute includes at least one of a straight-chain or branched dicarboxylic acid containing 8 to 30 carbon atoms and its ammonium salt, a monocarboxylic acid or polycarboxylic acid containing a benzene ring and its ammonium salt, dimethylamine, diethylamine, and triethylamine. For example, the solute can be selected from ammonium suberate, ammonium azelate, ammonium sebacate, ammonium dodecanedionate, C14, C16, C24, C30 fatty acids with single-end side branches or double-end side branches and their ammonium salts, dimethylamine, diethylamine, and triethylamine, preferably a branched tetradecanoic acid ammonium salt.
[0053] In some embodiments of the present invention, based on the total mass of the raw materials forming the electrolyte, the mass percentage of the solute is 25% to 38%. The mass percentage of the solute provided by the present invention can be the value of the interval composed of any two values in the above interval, such as 25% to 32%, or 32% to 38%, and so on. The mass percentage of the solute provided by the present invention can also be 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38% or any value that meets the above range value.
[0054] In some embodiments of the present invention, the auxiliary solute includes at least one of a linear polycarboxylic acid containing 5 to 35 carbon atoms and its ammonium salt, boric acid, ammonium borate, and ammonium pentaborate.
[0055] In some embodiments of the present invention, based on the total mass of each raw material forming the electrolyte, the mass percentage of the auxiliary solute is 2.6% to 4.2%. The mass percentage of the auxiliary solute provided by the present invention can be the value of the interval composed of any two values in the above interval, such as 2.6% to 3.2%, or 3.2% to 4.2%, and so on. The mass percentage of the auxiliary solute provided by the present invention can also be 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2% or any numerical value that meets the above range value.
[0056] In an embodiment of the present invention, the electrolyte for high temperature resistant capacitors further comprises at least one of a pH regulator, a waterproof mixture, a hydrogen remover and a slow-release agent.
[0057] In some embodiments of the present invention, the pH adjuster is selected from aqueous ammonia.
[0058] In some embodiments of the present invention, the mass percentage of the pH adjuster is 0.1% to 0.6% based on the total mass of the raw materials forming the electrolyte. The mass percentage of the pH adjuster provided by the present invention can be one of 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6% or any value that meets the above range.
[0059] In some embodiments of the present invention, the waterproofing mixture includes at least one of borates, phosphates, phosphoric acid, ammonium phosphate, phosphorous acid, ammonium phosphite, hypophosphorous acid, ammonium hypophosphite, ammonium hydrogen phosphate, polyphosphoric acid, ammonium polyphosphate salt, and alkyl phosphate.
[0060] In some embodiments of the present invention, the mass percentage of the waterproof mixture is 0.01% to 0.05% based on the total mass of the raw materials forming the electrolyte. The mass percentage of the waterproof mixture provided by the present invention can be one of 0.01%, 0.02%, 0.03%, 0.04%, 0.05% or any value satisfying the above range.
[0061] In some embodiments of the present invention, the hydrogen scavenger includes at least one of p-nitrophenol, m-nitrophenol, p-nitrobenzoic acid, o-nitroacetophenone, m-phenol, hydroquinone, o-nitroanisole, and p-nitrobenzyl alcohol.
[0062] In some embodiments of the present invention, based on the total mass of the raw materials forming the electrolyte, the mass percentage of the hydrogen remover is 0.1% to 0.6%. The mass percentage of the hydrogen remover provided by the present invention can be one of 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6% or any value satisfying the above range.
[0063] In some embodiments of the present invention, the sustained-release agent includes at least one of mannitol, sorbitol, xylitol, and sucrose.
[0064] In some embodiments of the present invention, based on the total mass of the raw materials forming the electrolyte, the mass percentage of the sustained-release agent is 1% to 4%. The mass percentage of the sustained-release agent provided by the present invention can be one of 1%, 2%, 3%, 4% or any value satisfying the above range.
[0065] In some embodiments of the present invention, the electrolyte for high temperature resistant capacitors includes a main solvent, an auxiliary solvent, a solute, an auxiliary solute, a flash voltage booster, a pH adjuster, a waterproof mixture, a hydrogen scavenger and a sustained release agent. The flash voltage booster includes a super-hydrophilic nano-modified silica sol. Based on the total mass of the raw materials forming the electrolyte, the mass percentage of the flash voltage booster is 10% to 18%, the mass percentage of the main solvent is 30% to 50%, the mass percentage of the auxiliary solvent is 1% to 5%, the mass percentage of the solute is 25% to 38%, the mass percentage of the auxiliary solute is 2.6% to 4.2%, the mass percentage of the pH adjuster is 0.1% to 0.6%, the mass percentage of the waterproof mixture is 0.01% to 0.05%, the mass percentage of the hydrogen scavenger is 0.1% to 0.6%, and the mass percentage of the sustained release agent is 1% to 4%.
[0066] The present invention also provides a method for preparing an electrolyte for a high temperature resistant capacitor, the key of which is to first synthesize a super-hydrophilic nano-modified silica sol, and then use the super-hydrophilic nano-modified silica sol as a flash voltage enhancer to prepare a capacitor electrolyte.
[0067] The preparation method of the super-hydrophilic nano-modified silica sol of the present invention is carried out according to the following steps.
[0068] (1) Preparation of acidic cross-linked super-hydrophilic nano-modified silica.
[0069] In an embodiment of the present invention, silica sol is dissolved in an alcohol solvent and the pH value is adjusted to 2-3, a silicon source precursor is added, the reaction is carried out under a first heating condition for a period of time, a surfactant is added, and the reaction is continued for a period of time to obtain acidic cross-linked super-hydrophilic nano-modified silica.
[0070] In some embodiments of the present invention, the alcohol solvent is selected from ethylene glycol.
[0071] It is worth mentioning that, considering that the main solvent used in the electrolyte system in the embodiment of the present invention is alcohols such as ethylene glycol, in order to avoid introducing impurities into the electrolyte system and affecting the performance of the electrolyte, ethylene glycol is used as the alcohol solvent in the synthesis and preparation of acidic cross-linked super-hydrophilic nano-modified silica.
[0072] In some embodiments of the present invention, the silica sol may be commercially available alcohol-soluble silica sol.
[0073] In the embodiment of the present invention, an acidic solution such as acetic acid, boric acid, or phosphoric acid is used to adjust the pH value to 2-3.
[0074] In some embodiments of the present invention, the silicon source precursor includes at least one of tetraethyl orthosilicate (TEOS) and tetramethyl orthosilicate.
[0075] In some embodiments of the present invention, the surfactant is selected from sodium C14-16 olefin sulfonate.
[0076] In an embodiment of the present invention, the mass ratio of the silicon source precursor to the surfactant may be 6.5 to 8.0:0.5 to 1.5. For example, the mass ratio of the silicon source precursor to the surfactant may be 6.5:0.5, 6.5:0.8, 6.5:1, 6.5:1.2, 6.5:1.5, 7:0.5, 7:0.8, 7:1, 7:1.2, 7:1.5, 7.5:0.5, 7.5:0.8, 7.5:1, 7.5:1.2, 7.5:1.5, 8:0.5, 8:0.8, 8:1, 8:1.2, 8:1.5, or any value satisfying the above range.
[0077] In some embodiments of the present invention, the mass ratio of tetraethyl orthosilicate to sodium C14-16 olefin sulfonate is 6.5-8.0:0.5-1.5.
[0078] In some embodiments of the present invention, the silica sol is dissolved in an alcohol solvent under magnetic stirring, for example, the stirring speed can be 1000 rpm to 1500 rpm, and the stirring time can be 10 min to 15 min. The stirring speed provided by the present invention can be one of 1000 rpm, 1100 rpm, 1200 rpm, 1300 rpm, 1400 rpm, 1500 rpm, or any value satisfying the above range. The stirring time provided by the present invention can be one of 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, or any value satisfying the above range.
[0079] In some embodiments of the present invention, the first heating can be water bath heating, and the heating temperature can be 40°C to 60°C. For example, the heating temperature can be one of 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C, 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C, 60°C or any value that meets the above range.
[0080] In some embodiments of the present invention, a silicon source precursor is added under a heating temperature of 40°C to 60°C, and the reaction is stirred for 1h to 2h, for example, the reaction is stirred for one of 1h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2h or any value that meets the above range.
[0081] In some embodiments of the present invention, the surfactant is added and the reaction is stirred for 24 to 26 hours while heating at a temperature of 40 to 60 degrees Celsius. For example, the reaction is stirred for 24 hours, 24.1 hours, 24.2 hours, 24.3 hours, 24.4 hours, 24.5 hours, 24.6 hours, 24.7 hours, 24.8 hours, 24.9 hours, 25 hours, 25.1 hours, 25.2 hours, 25.3 hours, 25.4 hours, 25.5 hours, 25.6 hours, 25.7 hours, 25.8 hours, 25.9 hours, 26 hours or any value satisfying the above range.
[0082] In an embodiment of the present invention, the preparation of acidic cross-linked super-hydrophilic nano-modified silica includes: adding alcohol-soluble silica sol and a certain amount of acidic solution to an alcohol solvent to adjust the solution pH to 2-3, magnetically stirring at a speed of 1000-1500 rpm for 10-15 min, adding a silicon source precursor, stirring and reacting at 40°C-60°C water bath conditions for 1h-2h, adding a surfactant, and continuing to stir and react at 40°C-60°C water bath conditions for 24h-26h to obtain acidic cross-linked super-hydrophilic nano-modified silica.
[0083] (2) Preparation of super-hydrophilic nano-modified silica sol.
[0084] In an embodiment of the present invention, the acidic cross-linked super-hydrophilic nano-modified silica and the aqueous transparent resin are reacted under the second heating condition to obtain the super-hydrophilic nano-modified silica sol.
[0085] In some embodiments of the present invention, the water-based transparent resin may be one or more of a water-based polyacrylic resin, a water-based fluorocarbon resin, a water-based amino resin, a water-based epoxy resin, and a water-based polyurethane resin.
[0086] In some embodiments of the present invention, the mass ratio of the acidic cross-linked super-hydrophilic nano-modified silica to the water-based transparent resin may be 100: 1 to 3. Exemplarily, the mass ratio of the acidic cross-linked super-hydrophilic nano-modified silica to the water-based transparent resin may be 100: 1, 100: 1.1, 100: 1.2, 100: 1.3, 100: 1.4, 100: 1.5, 100: 1.6, 100: 1.7, 100: 1.8, 100: 1.9, 100: 2, 100: 2.1, 100: 2.2, 100: 2.3, 100: 2.4, 100: 2.5, 100: 2.6, 100: 2.7, 100: 2.8, 100: 2.9, 100: 3 or any value satisfying the above range.
[0087] In some embodiments of the present invention, the second heating can be water bath heating, and the heating temperature can be 30°C to 50°C, for example, the heating temperature can be 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 38°C, 39°C, 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C, 50°C or any value that satisfies the above range. The heating time can be 2h to 4h, for example, the heating time can be 2h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h, 3h, 3.1h, 3.2h, 3.3h, 3.4h, 3.5h, 3.6h, 3.7h, 3.8h, 3.9h, 4h or any value that satisfies the above range.
[0088] In some embodiments of the present invention, an aqueous transparent resin is added to the acidic cross-linked super-hydrophilic nano-modified silica, and the mixture is stirred and reacted in a water bath at 30° C. to 50° C. for 2 h to 4 h to obtain a super-hydrophilic nano-modified silica sol.
[0089] In some embodiments of the present invention, the preparation of super-hydrophilic nano-modified silica sol includes: adding alcohol-soluble silica sol and a certain amount of acidic solution to an alcohol solvent to adjust the pH value of the solution to 2-3, adding a silicon source precursor after magnetic stirring, stirring and reacting for a period of time in a water bath at 40°C to 60°C, adding a surfactant, and continuing to stir and react for a period of time in a water bath at 40°C to 60°C to obtain acidic cross-linked super-hydrophilic nano-modified silica. Adding an aqueous transparent resin to the acidic cross-linked super-hydrophilic nano-modified silica, stirring and reacting at a water bath at 30°C to 50°C to obtain a super-hydrophilic nano-modified silica sol.
[0090] The preparation method of the electrolyte for high temperature resistant capacitors in the present invention is carried out according to the following steps.
[0091] S1. Mix the main solvent and the auxiliary solvent evenly.
[0092] In an embodiment of the present invention, the main solvent and the auxiliary solvent are uniformly mixed under the stirring conditions of 95°C to 105°C and a rotation speed of 300rmp to 400rmp to obtain a mixed solvent. The mixing temperature provided by the present invention can be one of 95°C, 100°C, 105°C or any value satisfying the above range. The stirring speed provided by the present invention can be one of 300rmp, 310rmp, 320rmp, 330rmp, 340rmp, 350rmp, 360rmp, 370rmp, 380rmp, 390rmp, 400rmp or any value satisfying the above range.
[0093] S2. Add solute and sustained-release agent to the mixed solvent at 95°C to 105°C, and stir until completely dissolved.
[0094] S3, adding waterproof mixture, hydrogen scavenger, auxiliary solute and flash voltage booster to the mixed solution obtained in step S2, and stirring at 95° C. to 105° C. for 30 min to 40 min.
[0095] In an embodiment of the present invention, the heat preservation and stirring time in step S3 can be one of 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, 36 min, 37 min, 38 min, 39 min, 40 min or any value that meets the above range.
[0096] S4. After the stirring in step S3 is completed, the mixed solution is cooled to 55° C. to 65° C., a pH adjuster is added, and the mixture is stirred for 5 min to 7 min at the same temperature to obtain an electrolyte for a high temperature resistant capacitor.
[0097] In an embodiment of the present invention, the temperature is lowered to 55° C. to 65° C. in step S4 , for example, the temperature can be lowered to one of 55° C., 60° C., 65° C. or any value satisfying the above range.
[0098] In an embodiment of the present invention, a pH adjuster is added in step S4 to adjust the pH value of the electrolyte to 6±3 to 7±3.
[0099] In an embodiment of the present invention, the stirring time in step S4 can be one of 5 min, 6 min, 7 min or any value satisfying the above range.
[0100] In an embodiment of the present invention, the main solvent and the auxiliary solvent are heated to 95°C to 105°C, stirred and mixed evenly at a speed of 300rpm to 400rpm, a sustained-release agent and a solute are added, and the temperature is maintained at 95°C to 105°C and stirred until the dissolution is complete, and then a waterproof mixture, a hydrogen scavenger, an auxiliary solute and a super-hydrophilic nano-modified silica sol are successively added. After dissolution, the mixture is stirred at 95°C to 105°C for 30min to 40min, and then cooled to 55°C to 65°C, a pH adjuster is added and stirred at this temperature for 5min to 7min, and finally an electrolyte for a high-temperature resistant capacitor is obtained.
[0101] The present invention also provides an aluminum electrolytic capacitor, which uses the high-temperature resistant capacitor electrolyte described in the present invention or the high-temperature resistant capacitor electrolyte prepared by the preparation method described in the present invention as a working electrolyte.
[0102] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The experimental reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the amounts of the experimental reagents, unless otherwise specified, are the amounts of reagents used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.
[0103] Example 1
[0104] The raw materials of the electrolyte for high temperature resistant capacitors include: 45.18g of ethylene glycol, 5g of diethylene glycol dimethyl ether, 27g of branched tetracarboxylic acid ammonium salt, 4g of ammonium sebacate, 0.2g of ammonium pentaborate, 15g of superhydrophilic nano-modified silica sol, 0.3g of ammonia water, 0.02g of phosphorous acid, 0.3g of o-nitroanisole, and 3g of mannitol. Among them, the superhydrophilic nano-modified silica sol is synthesized by using aqueous polyacrylic acid resin and acidic cross-linked superhydrophilic nano-modified silica in a mass ratio of 1:100.
[0105] The preparation method of super hydrophilic nano-modified silica sol is as follows:
[0106] To 80 mL of ethylene glycol, add 1 g of alcohol-soluble silica sol and a certain amount of acetic acid to adjust the pH value of the solution to 2, stir magnetically at a speed of 1000 rpm for 10 min, add 3 g of tetraethyl orthosilicate, stir and react in a water bath at 50 ° C for 1 h, add 0.4 g of C14-16 sodium olefin sulfonate, continue to stir and react in a water bath at 50 ° C for 24 h, and obtain acidic cross-linked super hydrophilic nano-modified silica.
[0107] 1 g of aqueous polyacrylic acid resin was added to 100 g of acidic cross-linked super-hydrophilic nano-modified silica, and the mixture was stirred and reacted for 2 h in a water bath at 40° C. to obtain a super-hydrophilic nano-modified silica sol.
[0108] The preparation method of the electrolyte for high temperature resistant capacitors is as follows:
[0109] Add 45.18g of ethylene glycol and 5g of diethylene glycol dimethyl ether into a beaker, heat to 100°C, stir and mix evenly at 400rpm, add 3g of mannitol and 27g of branched tetracarboxylic acid ammonium salt, keep stirring at 100°C until dissolved, then add 0.02g of phosphorous acid, 0.3g of o-nitroanisole, 4g of ammonium sebacate, 0.2g of ammonium pentaborate and 15g of superhydrophilic nano-modified silica sol successively, after dissolution, keep stirring at 100°C for 40min, cool to 60°C, add 0.3g of ammonia water and keep stirring for 5min to obtain an electrolyte for high temperature resistant capacitors.
[0110] Example 2
[0111] The remaining operations are the same as those in Example 1, except that the mass ratio of the aqueous polyacrylic acid resin to the acidic cross-linked super-hydrophilic nano-modified silica to form the super-hydrophilic nano-modified silica sol is 1.5:100; and 1.5 g of aqueous polyacrylic acid resin is added to 100 g of the acidic cross-linked super-hydrophilic nano-modified silica during the preparation.
[0112] Example 3
[0113] The remaining operations are the same as those in Example 1, except that the mass ratio of the aqueous polyacrylic acid resin to the acidic cross-linked super-hydrophilic nano-modified silica to form the super-hydrophilic nano-modified silica sol is 3:100; and 3 g of aqueous polyacrylic acid resin is added to 100 g of the acidic cross-linked super-hydrophilic nano-modified silica during the preparation.
[0114] Example 4
[0115] The remaining operations are the same as those in Example 1, except that: the superhydrophilic nano-modified silica sol is synthesized by using an aqueous fluorocarbon resin and an acidic cross-linked superhydrophilic nano-modified silica, and the mass ratio of the aqueous fluorocarbon resin to the acidic cross-linked superhydrophilic nano-modified silica is 1.5:100; during the preparation, 1.5 g of the aqueous fluorocarbon resin is added to 100 g of the acidic cross-linked superhydrophilic nano-modified silica.
[0116] Example 5
[0117] The remaining operations are the same as those in Example 1, except that: the superhydrophilic nano-modified silica sol is synthesized by using an aqueous amino resin and an acidic cross-linked superhydrophilic nano-modified silica, and the mass ratio of the aqueous amino resin to the acidic cross-linked superhydrophilic nano-modified silica is 1.5:100; during the preparation, 1.5 g of the aqueous amino resin is added to 100 g of the acidic cross-linked superhydrophilic nano-modified silica.
[0118] Example 6
[0119] The remaining operations are the same as those in Example 1, except that: the superhydrophilic nano-modified silica sol is synthesized by using an aqueous epoxy resin and an acidic cross-linked superhydrophilic nano-modified silica, and the mass ratio of the aqueous epoxy resin to the acidic cross-linked superhydrophilic nano-modified silica is 1.5:100; during the preparation, 1.5 g of aqueous epoxy resin is added to 100 g of the acidic cross-linked superhydrophilic nano-modified silica.
[0120] Example 7
[0121] The remaining operations are the same as those in Example 1, except that: the superhydrophilic nano-modified silica sol is synthesized by using an aqueous polyurethane resin and an acidic cross-linked superhydrophilic nano-modified silica, and the mass ratio of the aqueous polyurethane resin to the acidic cross-linked superhydrophilic nano-modified silica is 1.5:100; during the preparation, 1.5 g of the aqueous polyurethane resin is added to 100 g of the acidic cross-linked superhydrophilic nano-modified silica.
[0122] Comparative Example 1
[0123] The remaining operations are the same as those in Example 1, except that: the flash voltage enhancer uses 15 g of the acidic cross-linked super-hydrophilic nano-modified silica prepared in Example 1.
[0124] Comparative Example 2
[0125] The remaining operations are the same as those in Example 1, except that the flash voltage enhancer is 15 g of commercially available nano silicon dioxide.
[0126] Performance Testing:
[0127] Conductivity: Use a conductivity tester to test the conductivity of the electrolyte.
[0128] Flash voltage: Use a flash voltage tester to test the flash voltage of the electrolyte.
[0129] Conductivity change rate = ((conductivity after storage at 135° C. for 2000 h−conductivity before storage) / conductivity before storage)×100%.
[0130] In the present invention, the conductivity and the flash voltage of the electrolyte prepared in the embodiment and the comparative example are tested by a conductivity tester and a flash voltage tester, respectively. The test results are shown in Table 1.
[0131] Table 1 Summary of the performance of the electrolyte in the embodiments and comparative examples
[0132]
[0133] Generally, after high-temperature storage, if the solute is not resistant to high temperatures, it will be decomposed or react with other compounds in the electrolyte, resulting in a decrease in solute concentration and the addition of new impurities to reduce the conductivity of the system. It can be seen from Table 1 that in the present invention, due to the use of super-hydrophilic nano-modified silica sol, the change rate (decline rate) of the conductivity of the electrolyte after high-temperature storage is reduced, among which the conductivity change rate in Example 7 is the lowest, which is basically the same as before storage, and the performance is relatively excellent. Moreover, after high-temperature storage, the flash voltage basically maintains the same level as before storage, and even the flash voltage in Example 7 is slightly higher than before storage, which significantly improves the high-temperature storage performance of the electrolyte.
[0134] The super-hydrophilic nano-modified silica sol in the present invention is easy to hydrophilically combine with the oxide film in the anode foil. The super-hydrophilic structure makes the solution have excellent permeability to the oxide film, and it is easier to penetrate into the finer pores of the oxide film than ordinary nano-silicon dioxide, giving full play to the performance of silicon dioxide and macromolecular carboxylic acid. At the same time, the super-hydrophilic nano-modified silica sol of the present invention has better performance than acidic cross-linked super-hydrophilic nano-modified silica in the electrolyte system.
[0135] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.
Claims
1. An electrolyte, characterized in that: The invention comprises a main solvent, an auxiliary solvent, a solute, an auxiliary solute and a flash voltage enhancer, wherein the flash voltage enhancer comprises a super-hydrophilic nano-modified silica sol. Based on the total mass of the raw materials forming the electrolyte, the mass percentage of the flash voltage enhancer is 10% to 18%.
2. The electrolyte according to claim 1, characterized in that Based on the total mass of the raw materials forming the electrolyte, the mass percentage of the main solvent is 30% to 50%, the mass percentage of the auxiliary solvent is 1% to 5%, the mass percentage of the solute is 25% to 38%, and the mass percentage of the auxiliary solute is 2.6% to 4.2%.
3. The electrolyte according to claim 1, characterized in that The super-hydrophilic nano-modified silica sol is obtained by reacting acidic cross-linked super-hydrophilic nano-modified silica with a water-based transparent resin; Preferably, the water-based transparent resin includes at least one of a water-based polyacrylic resin, a water-based fluorocarbon resin, a water-based amino resin, a water-based epoxy resin, and a water-based polyurethane resin.
4. The electrolyte according to claim 1, characterized in that The main solvent includes at least one of ethylene glycol, tripropylene glycol, diethylene glycol, propylene glycol, and glycerol; Preferably, the auxiliary solvent includes at least one of alcohols, alcohol ethers, amides, lactones, sulfolane, N-methylpyrrolidone, and dimethyl sulfoxide; Preferably, the solute includes at least one of a straight-chain or branched dicarboxylic acid containing 8 to 30 carbon atoms and its ammonium salt, a monocarboxylic or polycarboxylic acid containing a benzene ring and its ammonium salt, dimethylamine, diethylamine, and triethylamine; Preferably, the auxiliary solute includes at least one of a linear polycarboxylic acid containing 5 to 35 carbon atoms and its ammonium salt, boric acid, ammonium borate, and ammonium pentaborate.
5. The electrolyte according to claim 1, characterized in that The electrolyte further comprises at least one of a pH regulator, a waterproofing agent, a hydrogen remover and a slow-release agent; Preferably, the pH regulator is selected from aqueous ammonia; Preferably, the waterproofing mixture includes at least one of borate, phosphate, phosphoric acid, ammonium phosphate, phosphorous acid, ammonium phosphite, hypophosphorous acid, ammonium hypophosphite, ammonium hydrogen phosphate, polyphosphoric acid, ammonium polyphosphate salt, and alkyl phosphate; Preferably, the hydrogen remover comprises at least one of p-nitrophenol, m-nitrophenol, p-nitrobenzoic acid, o-nitroacetophenone, m-phenol, hydroquinone, o-nitroanisole, and p-nitrobenzyl alcohol; Preferably, the sustained-release agent comprises at least one of mannitol, sorbitol, xylitol and sucrose.
6. The electrolyte according to claim 5, characterized in that Based on the total mass of the raw materials forming the electrolyte, the mass percentage of the pH regulator is 0.1% to 0.6%, the mass percentage of the waterproof mixture is 0.01% to 0.05%, the mass percentage of the hydrogen remover is 0.1% to 0.6%, and the mass percentage of the sustained-release agent is 1% to 4%.
7. A method for preparing the electrolyte according to any one of claims 1 to 6, characterized in that: The preparation method comprises: After the main solvent and the auxiliary solvent are evenly mixed, the solute, the auxiliary solute and the flash voltage enhancer are added at 95°C to 105°C and stirred until the dissolution is complete.
8. The preparation method according to claim 7, characterized in that: The preparation method further comprises preparing a super-hydrophilic nano-modified silica sol, and the preparation of the super-hydrophilic nano-modified silica sol comprises: Dissolving silica sol in an alcohol solvent and adjusting the pH value to 2-3, adding a silicon source precursor, reacting for a period of time under a first heating condition, adding a surfactant, and keeping the temperature for a period of time to obtain an acidic cross-linked super-hydrophilic nano-modified silica; reacting the acidic cross-linked super-hydrophilic nano-modified silica with an aqueous transparent resin under a second heating condition to obtain a super-hydrophilic nano-modified silica sol; Preferably, the silicon source precursor includes at least one of tetraethyl orthosilicate and tetramethyl orthosilicate; Preferably, the alcohol solvent is selected from ethylene glycol; Preferably, the surfactant is selected from sodium C14-16 olefin sulfonate; Preferably, the mass ratio of the silicon source precursor to the surfactant is 6.5-8.0:0.5-1.5; Preferably, the first heating temperature is 40° C. to 60° C.; preferably, the silicon source precursor is reacted for 1 h to 2 h after being added, and the surfactant is reacted for 24 h to 26 h after being added; Preferably, the mass ratio of the acidic cross-linked super-hydrophilic nano-modified silica to the water-based transparent resin is 100:1-3; Preferably, the second heating temperature is 30° C. to 50° C., and the second heating time is 2 h to 4 h.
9. The preparation method according to claim 7, characterized in that: The preparation method also includes: after the main solvent and the auxiliary solvent are evenly mixed, a solute and a sustained-release agent are added at 95° C. to 105° C., after complete dissolution, a waterproofing mixture, a hydrogen scavenger, an auxiliary solute and a flash voltage enhancer are added, the temperature is reduced to 55° C. to 65° C., and a pH regulator is added to obtain the electrolyte.
10. An aluminum electrolytic capacitor, characterized in that: The aluminum electrolytic capacitor uses the electrolyte described in any one of claims 1 to 6 or the electrolyte prepared by the preparation method described in any one of claims 7 to 9 as a working electrolyte.